PEMETAAN PEMANGKU KEPENTINGAN: ANALISIS VISUAL BRANDING UNTUK MENINGKATKAN KETERLIBATAN MASYARAKAT DI KOTA CIREBON: Stakeholder Mapping: Visual Analysis of Branding to Enhance Community Engagement in the City of Cirebon - Budi Suyanto; Myrza Rahmanita; Suyanto, Budi (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2024)
Tourism in Cirebon City, Indonesia, is an important focus in supporting economic growth. The foreign exchange contribution of the tourism sector reached 18.4 billion USD in 2019, showing great potential. The government has taken policy steps, utilizing regional autonomy. Analysis of branding strategies shows that the involvement of stakeholders, including local communities, is important in shaping the destination's image. This research explores the role of visual branding in Cirebon City, focusing on stakeholder collaboration as the key to success. Stakeholders' expectations and views were the subject of questions. The results are expected to provide insights to improve community engagement and sustainable tourism development.